Environmental security - Hossain, Ishtiaq (2019)
Beyond traditional national (military) security, there are growing concerns regarding nontraditional military security issues such as human security, economic security, social security, information security, and environmental security. Among the non-traditional security issues, however, environmental security stands out as one of the most critical concerns that transcends national boundaries, affects all societies, and has international conventions affecting all states. Concerns such as ecological disorders and natural disasters – including water and air pollution, land degradation, deforestation,global warming, ozone depletion, sea-level rise, biodiversity loss, resource scarcity, economic well-being, trans-state criminal organizations and the mass migration of people– threaten the very sustainability of human progress.